Bilio-bronchial and bilio-pleuro-bronchial fistulas of hydatic origin - Massine El Hammoumi; El Hassane Kabiri (Termedia Publishing House, 2022)
Bilio-bronchial fistulization is a rare complication of neglected liver hydatid cysts ruptured in the thorax by anatomical contiguity. Because of the bronchopulmonary and hepato-biliary lesions that it can cause and in the context of severe infection, the morbi-mortality remains high in these fragile patients. The diagnosis is based on clinical arguments: biliptysis mainly with a hepato-thoracic syndrome, imaging data showing the fistulous path, and especially bronchial and biliary endoscopy. The pretherapeutic stage aims at correcting the hydrolytic, anemic and nutritional defects, but above all at controlling the hepatobronchial infection after removal of the biliary obstruction (endoscopic sphincterotomy) and by broad-spectrum antibiotic therapy as well as active respiratory physiotherapy. This preparatory step may be sufficient, otherwise surgical sanction is necessary in operable patients to establish the hepato-phreno-thoracic disconnection. The choice of the thoracic or abdominal approach depends on the initial and progressive lesion assessment and on the surgical strategy envisaged.